2022
DOI: 10.3390/ijms23137119
|View full text |Cite
|
Sign up to set email alerts
|

Shear Stress Enhances the Paracrine-Mediated Immunoregulatory Function of Human Periodontal Ligament Stem Cells via the ERK Signalling Pathway

Abstract: Relevant immunomodulatory effects have been proposed following allogeneic cell-based therapy with human periodontal ligament stem cells (hPDLSCs). This study aimed to examine the influence of shear stress on the immunosuppressive capacity of hPDLSCs. Cells were subjected to shear stress at different magnitudes (0.5, 5 and 10 dyn/cm2). The expression of immunosuppressive markers was evaluated in shear stress-induced hPDLSCs using qRT-PCR, western blot, enzyme activity and enzyme-linked immunosorbent assays. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 71 publications
(107 reference statements)
1
6
0
Order By: Relevance
“…In this study, we con rmed that OSS promotes the formation of early and lately AS plaques in ApoE-/-mice by oil red staining analysis and immunohistochemical and immuno uorescence staining found that OSS activates the EndMT process and regulates ID1 protein expression. Multiple studies have shown that TGF-β signalling is enriched in the OSS region (Deng et al, 2021), (Suwittayarak et al, 2022), which is consistent with our immunohistochemical results. We used TGF-β1 to act on HAECs to simulate a low oscillating shear stress environment in vitro.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we con rmed that OSS promotes the formation of early and lately AS plaques in ApoE-/-mice by oil red staining analysis and immunohistochemical and immuno uorescence staining found that OSS activates the EndMT process and regulates ID1 protein expression. Multiple studies have shown that TGF-β signalling is enriched in the OSS region (Deng et al, 2021), (Suwittayarak et al, 2022), which is consistent with our immunohistochemical results. We used TGF-β1 to act on HAECs to simulate a low oscillating shear stress environment in vitro.…”
Section: Discussionsupporting
confidence: 93%
“…All experiments were repeated using the cells derived from at least four different donors (n = 4; Manokawinchoke et al, 2019Manokawinchoke et al, , 2020Suwittayarak et al, 2022). The statistical analysis was performed using Prism 8 (GraphPad Software).…”
Section: Discussionmentioning
confidence: 99%
“…Naringin, at a dose of 1 µM, can promote the proliferation and differentiation of hPDLSCs into osteoblasts, as indicated by upregulating bone-related factors, such as RUNX2, COL1A2, OPN, and OCN [38]. However, the limited lifespan of hPDLSCs restricts their application [39]. The knock-in of Bmil may enhance the cell cycle, cell replication, and stemness of hPDLSCs.…”
Section: Osteogenic Differentiation Inductionmentioning
confidence: 99%